RNA interference in cytochrome P450 monooxygenase (CYP) gene results in reduced insecticide resistance in Megalurothrips usitatus Bagnall - Chen, Weiyi; Li, Zhaoyang; Zhou, Chenyan; Ali, Asad; Ali, Shaukat; Wu, Jianhui (Frontiers in Physiology, 2023)
Genes of the cytochrome P450 (CYP450) superfamily are known to be involved in the evolution of insecticide resistance. In this study, the transcriptomes of two Megalurothrips usitatus Bagnall (Thysanoptera: Thripidae) strains (resistant and susceptible) were screened for detoxification genes. MusiDN2722 encodes a protein composed of 504 amino acid residues with a relative molecular mass of 57.3 kDa. Multiple sequence alignment and phylogenetic analysis showed that MusiDN2722 is a member of the CYP450 family and has characteristics of the conserved CYP6 domain shared by typical CYP450 family members. RT-qPCR (real-time quantitative polymerase chain reaction) analysis showed that MusiDN2722 was upregulated in the acetamiprid-resistant strain compared with the susceptible strain (p < 0.05), and the relative expression level was significantly higher at 48 h after exposure than at 24 h after exposure. The interference efficiency of the injection method was higher than that of the membrane-feeding method. Silencing of MusiDN2722 through RNA interference significantly increased the sensitivity of M. usitatus to acetamiprid. Overall, this study revealed that MusiDN2722 plays a crucial role in the resistance of M. usitatus to acetamiprid. The findings will not only advance our understanding of the role of P450s in insecticide resistance but also provide a potential target for the sustainable control of destructive pests such as thrips.